Design of an evaluation model for self-evaluation processes of medical specialties at the University of Costa Rica, from a right to education approach (Educational Knowledge, 2017)
This article discusses the relevance of adopting a human rights approach, particularly the right to education, for designing a model for the self-evaluation processes of medical specialties at the University of Costa Rica. The model emphasizes four characteristics—and their related elements—that safeguard the right to education: availability, accessibility, acceptability, and adaptability. It then explores how, based on the realities of the medical specialties context, these four characteristics will be considered in the self-evaluation model.
Keywords: human rights; self-evaluation; right to education model; medical specialties